Persepsi Siswa Terhadap Kompetensi Guru Dalam Pembelajaran Ekonomi Pada SMA Negeri 13 Banda Aceh - Sariyani Sariyani; Musfiana Musfiana; Alfi Syahril FJ (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
The research entitled "Student Perceptions on Teacher Competence in Economic Learning at State Senior High School 13 Banda Aceh" aims to see how the students' perceptions of teacher competence, especially in the field of pedagogic. The population of this study is all students of IPS which amounted to 26 students, while the sample in this study is the entire population, so this study is a population study (total sampling) and the approach done in this research is quantitative approach with descriptive research type. Technique of collecting data in this research is done by library research, preliminary observation and spreading of questionnaire / questionnaire. Data analysis using simple statistic that is percentage (%) and average (Mx). Based on the results of the study showed that, understanding of the students is categorized very well with an average value of 4.18, effective communication with learners is categorized very well with an average value of 4.22 curriculum development categorized good 3.88, the implementation of learning that educate And dialogically categorized very well with the average score 4.31, master the theory of learning is categorized very well with the average value 4.44, evaluation of learning outcomes is categorized very well denagan average value 4.26, and the development of learners to actualize Various potentials are categorized very well with an average value of 4.43.